Nomogram constructed by immunological and inflammatory indicators for predicting prognosis of patients with esophageal squamous cell carcinoma treated with neoadjuvant chemoradiotherapy plus surgery - Luo, Yun; Weng, Xue-Fen; Huang, Jia-Tao; Hu, Xue-Hao; Wei, Lai-Feng; Lin, Yi-Wei; Ding, Tian-Yan; Zhang, Biao; Chu, Ling-Yu; Liu, Can-Tong; Peng, Yu-Hui; Xu, Yi-Wei; et al. (Frontiers in Oncology, 2022)
Objectives At present, esophageal squamous cell carcinoma (ESCC) patients accepting neoadjuvant chemoradiotherapy (nCRT) plus surgery lack corresponding prognostic indicators. This study aimed to construct a prognostic prediction model for ESCC patients undergoing nCRT and surgery based on immune and inflammation-related indicators. Methods We retrospectively analyzed the levels of serum immune- and inflammation-related indicators of ESCC patients before receiving nCRT plus surgery in the training cohort (99 patients) and validation cohort (67 patients), which were collected from 2007 to 2020. Univariate and multivariate Cox survival analyses were conducted to evaluate the indicators to set up a nomogram associated with the patients’ overall survival (OS). The prediction accuracy and discriminative ability of the nomogram were measured by the concordance index (C-index), decision curve, calibration curve, integrated discrimination improvement (IDI), and net reclassification improvement (NRI). Results Univariate and multivariate Cox analyses demonstrated that immune globin A (IgA) and C-reactive protein (CRP) were independent risk factors. A nomogram based on IgA, CRP, and cTNM stage was established for predicted OS in the training cohort and validated in the validation cohort. The C-index of the nomogram was 0.820 (95% CI: 0.705–0.934), which was higher than that of the cTNM stage (0.655 (95% CI: 0.546–0.764), p < 0.05) in the training cohort, and similar results were observed in the validation cohort (0.832 (95% CI: 0.760–0.903 vs 0.635 (95% CI: 0.509–0.757), p < 0.001). Furthermore, the prediction accuracy and net benefit of the nomogram verified by the calibration curve, decision curve, NRI, and IDI were satisfactory in the training and validation cohorts. Conclusion The newly constructed nomogram concluding serum IgA, CRP, and cTNM stage might be helpful in the prognosis prediction for ESCC patients receiving nCRT plus surgery.